Answer: 2x^2
The three terms are
2x^2
-3x
5
as they are separated by a plus sign. You can think of it as 2x^2 + (-3x) + 5 if you want. The quadratic term is the term with the exponent of 2
Answer:
(x - 12)²/9
Step-by-step explanation:
y = 3sqr(x) + 12
Make x the subject:
y - 12 = 3sqrt(x)
(y - 12)/3 = sqrt(x)
Square both sides
(y - 12)²/9 = x
Interswitch variables
inverse function is:
(x - 12)²/9
If f(x) = (x + 12)^⅓
Then,
y = (x + 12)⅓
y³ = x + 12
y³ - 12 = x
f inverse:
x³ - 12
Answer:
-6 -7 -8 -9 -10
Step-by-step explanation:
anything that keeps going from there dont do anything like -5 -4 -3 -2 -1 because it would be wrong
any negative number that keeps increasing after -6
Answer:
$28.9
I hope this help also I would appreciate brainliest if possible :)